Strategy for New Technology Release by Integrating Consumer Demand to Product Roadmap - Udiyarsa, Dedhi; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2013)
Broadband, mobility and the cloud connect people and places, as well as applications and devices. Due to rapid demand in the Information and Telecommunication technology Industry, the technology lifecycle management has to be defined optimally. This final project will try to answer what is the optimal product release strategy should be applied to accommodate the customer requirement in RASO (Regional South East Asia and Oceania). This final project also answer how to define and apply optimized product release strategy based on the customer requirement and Roger’s theory. Survey for the customer demand is conducted to answer those requirements. Based on Roger’s bell curve from Diffusion of Innovation theory, the alternative strategy to introduce new technology to the customer will be defined. Effective product releases should be applied for the customer requirement in RASO is defined by Provide one official release in a year; still maintained minor release to as the backup release; customization and adaptation for the customer requirement and the competitor capability. The strategy for the product release are defined and applied with first of application sponsorship, pay as you use and licensing, revenue sharing, and or reference of the business model by business model canvas. This project also recommended, Customer in RASO is positioning their company as the innovator or early adopter of the new technology. Alternative solution is needed to support implementation of the new technology. It convinces customer to acquire new technology in the very first phase. By using the alternative solution, customer requirement will be fulfilled to support business growth and customer business objective. Keywords: new technology introduction strategy, product lifecycle roadmap, product release strategy